Jewish Identity and Palestinian Rights : Diaspora Jewish Opposition to Israel. - Landy, David (Zed Books Ltd., 2011)
Diaspora Jews are increasingly likely to criticise Israel and support Palestinian rights. In the USA, Europe and elsewhere, Jewish organisations have sprung up to oppose Israel's treatment of Palestinians, facing harsh criticism from fellow Jews for their actions. Jewish Identity and Palestinian Rights is a groundbreaking study of this vital and growing worldwide social movement.